Double Difference (DD) Fixed Effects Method in Micro Loans on Household Income in Indonesia - Suratini Suratini; Jolyne Myrell Parera (MediaTrend, 2022)
Micro-loans are loans aimed at helping poor or low-income communities to increase their income through increasing productivity so as to reduce poverty. The purpose of this study is to determine the relationship of micro-loans to the increase in household income per capita in Indonesia and to determine the impact of micro-loans that actually result in an increase in household income per capita in Indonesia. The method used is Double Difference (DD) Fixed Effects with data from the Indonesia Family Life Survey (IFLS) in 2000 and 2007. The estimation results show that it is proven that the impact of micro loans on income changes is not visible and even looks negative 0.446. There was an increase in total income in 2007 compared to 2000 with a coefficient value of 0.279 using the nominal value. However, in real terms, the coefficient value is not significant, namely negative 0.063.